1998
DOI: 10.1080/15216549800201202
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine palmitoyltransferase II activity is decreased in liver mitochondria of cachectic rats bearing the Walker 256 carcinosarcoma: Effect of indomethacin treatment

Abstract: Summary. The syndrome of cancer cachexia is accompanied by several alterations of lipid metabolism, especially that in the liver. In this study we have investigated a possible mechanism whereby the presence of the Walker 256 carcinosarcoma affects hepatic fatty acid oxidative capacity in tumour-bearing rats. Hepatic mitochondrial outer membrane carnitine palmitoyltransferase I (CPT I), generally accepted as the main site of regulation of fatty acid oxidation, was unaffected by the presence of the extra-hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2
9

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 21 publications
(28 reference statements)
3
45
2
9
Order By: Relevance
“…Steatosis 26,30 and reductions in fatty acid oxidation/oxidative capacity 25,27,59 in the liver have been reported in the Walker 256 carcinosarcoma cachexia model when weight loss was substantial. In our study of early cachexia, markers of fatty acid oxidation were increased in liver and measurements of hepatic total lipids were not different among groups.…”
Section: Discussionmentioning
confidence: 99%
“…Steatosis 26,30 and reductions in fatty acid oxidation/oxidative capacity 25,27,59 in the liver have been reported in the Walker 256 carcinosarcoma cachexia model when weight loss was substantial. In our study of early cachexia, markers of fatty acid oxidation were increased in liver and measurements of hepatic total lipids were not different among groups.…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, FAO in liver diseases is mainly limited by CPT 2. Seelaender et al have also found that CPT 2 activity shrank in rats bearing the Walker 256 carcinosarcoma and the expression of CPT 2 may be affected by a prostaglandin, PGE(2) [48].…”
Section: Alterations Of Serum Acylcarnitine Level Among Hcc and Cldmentioning
confidence: 99%
“…Walker 256 tumour cells (2!10 7 cells) were injected s.c. into the right flank of the animals (Seelaender et al 1998). Control rats received saline injections on the same day of tumour inoculation.…”
Section: Animalsmentioning
confidence: 99%